Low maternal vitamin D status and fetal bone development: cohort study. - Mahon, P; Harvey, N; Crozier, S; Inskip, H; Robinson, S; Arden, N; Swaminathan, R; Cooper, C; Godfrey, K (2010)
Recent findings suggest that maternal vitamin D insufficiency during pregnancy has consequences for the offspring's bone health in later life. To investigate whether maternal vitamin D insufficiency affects fetal femur growth in ways similar to those seen in childhood rickets and study the timing during gestation of any effect of maternal vitamin D status, we studied 424 pregnant women within a prospective longitudinal study of maternal nutrition and lifestyle before and during pregnancy (Southampton Women's Survey). Using high-resolution 3D ultrasound, we measured fetal femur length and distal metaphyseal cross-sectional area, together with the ratio of femoral metaphyseal cross-sectional area to femur length (femoral splaying index). Lower maternal 25-hydroxyvitamin vitamin D concentration was not related to fetal femur length but was associated with greater femoral metaphyseal cross-sectional area and a higher femoral splaying index at 19 weeks' gestation [r = -0.16, 95% confidence interval (CI) -0.25 to -0.06 and r = -0.17, 95% CI -0.26 to -0.07, respectively] and at 34 weeks' gestation (r = -0.10, 95% CI -0.20 to 0.00 and r = -0.11, 95% CI -0.21 to -0.01, respectively). Three groups of women were identified with 25-hydroxyvitamin vitamin D concentrations that were sufficient/borderline (> 50 nmol/L, 63.4%), insufficient (25 to 50 nmol/L, 30.7%), and deficient (< or = 25 nmol/L, 5.9%). Across these groups, the geometric mean femoral splaying indices at 19 weeks' gestation increased from 0.074 (sufficient/borderline) to 0.078 (insufficient) and 0.084 (deficient). Our observations suggest that maternal vitamin D insufficiency can influence fetal femoral development as early as 19 weeks' gestation. This suggests that measures to improve maternal vitamin D status should be instituted in early pregnancy.